2020
DOI: 10.3390/ijms21176326
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant and Non-Resistant Bacteria Display Similar Susceptibility to Dielectric Barrier Discharge Plasma

Abstract: Here, we examined whether antibiotic-resistant and non-resistant bacteria show a differential susceptibility to plasma treatment. Escherichia coli DH5α were transformed with pPRO-EX-HT-CAT, which encodes an ampicillin resistance gene and chloramphenicol acetyltransferase (CAT) gene, and then treated with a dielectric barrier discharge (DBD) plasma torch. Plasma treatment reduced the viable cell count of E. coli after transformation/selection and further cultured in ampicillin-containing and ampicillin-free med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…It is also demonstrated that plasma multi jets can be a potent bactericidal agent for native or mature bacterial lawns contaminated with a single but also a mix of various pathogens. Similar efficiency was demonstrated for antibiotic-resistant and non-resistant P. aeruginosa (see Figure 9) as previously reported but for E. coli bacteria and with dielectric barrier discharge applicator [33]. This strengthens the well-known unique status of plasma technology in comparison with conventional antibiotic drugs, as a broad spectrum and non-systemic, and thus likely a low side-effect, therapeutic option.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is also demonstrated that plasma multi jets can be a potent bactericidal agent for native or mature bacterial lawns contaminated with a single but also a mix of various pathogens. Similar efficiency was demonstrated for antibiotic-resistant and non-resistant P. aeruginosa (see Figure 9) as previously reported but for E. coli bacteria and with dielectric barrier discharge applicator [33]. This strengthens the well-known unique status of plasma technology in comparison with conventional antibiotic drugs, as a broad spectrum and non-systemic, and thus likely a low side-effect, therapeutic option.…”
Section: Discussionsupporting
confidence: 88%
“…Planktonic or biofilm growth on borosilicate slides cultured in 24-well plates were considered in this work, and a combination of plasma treatment with antibiotics was also evaluated. In [33], a dielectric barrier discharge (DBD) plasma torch generated with an air flow at 3.5 L/min and delivering a plasma jet 4 mm in diameter was used to study the sensitivity of antibiotic-resistant and non-resistant bacteria. The microorganisms were set in a thin liquid layer covering a glass substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies by the likes of Socransky et al. [ 44 ] amongst others have found that various types of bacteria like P. aeruginosa [ 45 ], Staphylococcus aureus [ 4 ], Escherichia Coli [ 4 , 46 ] , Enterococcus faecalis [ 47 ], can be inactivated by plasma, as mentioned in Table 2 .…”
Section: Application Of Ntp In Dentistrymentioning
confidence: 99%
“…An air DBD-based indirect LTP source is shown in Fig. 1(c) [32]. A commercial version of this type of LTP is the PlasmaDerm device.…”
Section: Introductionmentioning
confidence: 99%